Fata morgana‘s van de auteursintentie: Intentieprocessen als valkuil voor biografisch en teksteditorisch onderzoek - T‘Sjoen, Yves; De Potter, Linde (Department of Dutch and South African Studies, Faculty of English, 2013)
The notion “author’s intention” is nothing less than a booby trap. Intention counts as a diffuse concept for literary research. In editorial theory and the practical application of it, scholars use concepts such as “intended meaning” and “authorial intention” in order to legitimize certain decisions concerning the choice of the text version and the determination of variants respectively typographical errors. Contemporary research on text editing distinguishes between “authorial will” and “authorial intention” (Mathijsen 1995: 141-142). Not the (testamentary) will of the author will be decisive in order to edit or interpret a certain text (version): the focus lies on what the author has “intended.” This differentiation between “will” (a legal concept) and “intention” (a psychological category) is clear. Nevertheless, it has been neglected regularly by biographers (of a more “hagiographic” and psychologizing kind). In this view, biographical and editorial research, and even literary history show dubious similarities. These research disciplines pretend to be able to know and study intentions and opinions of an author. Notwithstanding these similarities and points of view, biographers almost never make use of the results of text genetics. For a scholarly discipline, it is at least remarkable that some biographers and editors rely on hypotheses and speculations in order to express textual decisions.
Keywords: authorial intention; editorial theory; intentional fallacy; literary biography; literary historiography; genetic criticism